Preparation and Characterization of low-cost activated carbon prepared from Skin of Allium sativum and Zingiber officinale (International Journal of Food and Nutritional Sciences, 2022)
Activated carbon was prepared from skin of Allium sativum and Zingiber officinale. Pottasium hydroxide is widely used as an activating agent for preparation of activated carbon. The microscopic and spectroscopic methods such as BET, XRD, TGA/DTA, FT-IR, and SEM with EDAX, aspect of their power to directly view the micro-structure of activated carbons have huge potential for utilize in the inquiry and characterization of AC. Using BET method to determine the surface area, pore volume